THE EFFECT OF ECAP PROCESSING TO HARDNESS, SURFACE MORPHOLOGI, AND CORROSION RESISTANCE OF 6061 ALUMINIUM ALLOYS - Vinda Puspasari; I. Nyoman Gede P. A.; Efendi Mabruri; Satrio Herbirowo; Edy Priyanto Utomo (Metalurgi, 2021)
Al-Mg-Si alloys (6xxx) has been widely used as structural materials in building and vehicles because of its excellent strength and corrosion resistance. The improvement of fine grain microstructure which can increase mechanical and physical properties become an interesting field in recent research.. Equal channel angular press is the most promising method to apply severe plastic deformation (SPD) which can produce ultra-fine grain in the bulk material without residual porosity. This study presents some experiments results on the effect of ECAP number of passes variation to the hardness, microstructure, and corrosion behaviour of Al 6061 alloys. The samples were annealed in the furnace with argon gas environment at 530°C for 4 hours and then immersed in liquid nitrogen for 5 minutes before ECAP process. The ECAP process was done with Bc route using dies with 120° of internal channel angle and pass variation of 1, 2, 3, and 4. The optimum hardness is 107.58 HRB in Al 6061 samples with 3 passes of ECAP. The increasing ECAP number of passes leads to a significant grain size reduction from 0 way pass, the grain size is around 10 µm, while for a 4 way pass, the grain size is around 2.5 µm. The corrosion resistance of Al 6061 alloys increased with the increasing number of passes in ECAP process.